2010
DOI: 10.1007/s00521-010-0444-y
|View full text |Cite
|
Sign up to set email alerts
|

Short-term load forecasting of power systems by gene expression programming

Abstract: Short-term load forecasting is a popular topic in the electric power industry due to its essentiality in energy system planning and operation. Load forecasting is important in deregulated power systems since an improvement of a few percentages in the prediction accuracy will bring benefits worth of millions of dollars. In this study, a promising variant of genetic programming, namely gene expression programming (GEP), is utilized to improve the accuracy and enhance the robustness of load forecasting results. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Fan and Zhu indicated that a combination of empirical mode decomposition (EMD) and GEP may perform higher accuracy than WD and GEP combination for short-term load forecasting [23]. Hosseini and Gandomi compared GEP models with multiple least squares regression (MLSR) and generalized regression neural networks (GRNN) for forecasting day ahead peak and total loads of a North American electric utility [24]. Deng et al used artificial fish swarm based hybrid GEP along with cloud computing in order to model distributed electric load forecasting in comparison with ANN, PSO-SVM, SVR, and traditional GEP on the data set of EUNITE competition [25].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Fan and Zhu indicated that a combination of empirical mode decomposition (EMD) and GEP may perform higher accuracy than WD and GEP combination for short-term load forecasting [23]. Hosseini and Gandomi compared GEP models with multiple least squares regression (MLSR) and generalized regression neural networks (GRNN) for forecasting day ahead peak and total loads of a North American electric utility [24]. Deng et al used artificial fish swarm based hybrid GEP along with cloud computing in order to model distributed electric load forecasting in comparison with ANN, PSO-SVM, SVR, and traditional GEP on the data set of EUNITE competition [25].…”
Section: Related Workmentioning
confidence: 99%
“…Although parse tree demonstration is used in traditional GP, GEP employs a fixed length of character strings ([+, *, *, β 1 ,x 1 , β 2 , x 2 ] for the expression tree in Figure 4) for illustrating solutions to the problems, which are then visualized as parse trees [24]. The illustration of trees in GEP is named as expression tree and shown in Figure 4.…”
Section: Gene Expression Programmingmentioning
confidence: 99%
“…A basic representation of the GEP algorithm is presented in Fig. 4 [26]. In GEP, the individuals are selected and copied into the next generation according to the fitness by roulette wheel sampling with elitism.…”
Section: Gene Expression Programmingmentioning
confidence: 99%
“…Because of its high performance, GEP has attracted increasing attention recently as an efficient and effective data mining approach. Moreover, it has been successfully applied to many fields, such as function finding [7][8][9], symbolic regression [10][11][12][13], parameter optimization [14], rule mining [15], classification [3,16], time series forecasting [2], prediction of flow number of asphalt mixes [17], prediction of material load [18,19], prediction of the strength of concrete [20], engineering design [21], and machine scheduling [22,23].…”
Section: Introductionmentioning
confidence: 99%